THE LAW ON SELLING SUBSIDIZED OIL USING JERRY CANS BASED ON PRESIDENTIAL DECREE NUMBER 117 OF 2021 CONCERNING THE PROVISION, DISTRIBUTION, AND RETAIL SELLING PRICES OF FUEL OIL FROM THE PERSPECTIVE OF SADD ADZ-DZARI'AH - Roqiqoh Paco Negara; Rahmat Hidayat (Program Pascasarjana UIN Sumatera Utara, 2025)
Subsidized fuel is often purchased using jerry cans at gas stations and resold to vehicle users at prices much higher than the price set by the Government. This is not permitted without a specific permit, as regulated in Presidential Decree No. 117 of 2021 concerning Retail Selling Prices and Consumers Using Certain Types of Fuel Oil. The purpose of this study is why the government prohibits the sale of subsidized fuel using jerry cans, then and what is the effect of the ban on the sale of subsidized fuel using jerry cans at gas stations. What is the perspective of Presidential Decree No. 117 of 2021 and Sadd Adz-dzari'ah regarding the prohibition on the sale of subsidized fuel using jerry cans. This type of research is normative juridical, with data collected through document studies and then processed using qualitative methods. The results of the study indicate that the reason the government prohibits the public from purchasing subsidized fuel using containers that do not comply with standards is because it can cause negative impacts such as flammability, environmental pollution and fuel hoarding. Presidential Decree No. Law No. 117 of 2021 concerning the prohibition on the sale of subsidized fuel using containers that do not meet regulatory standards aligns with the concept of Sadd Adz-dzari'ah, where the government implements the ban from a Sadd Adz-dzari'ah perspective. Sadd Adz-dzari'ah emphasizes the importance of preventing actions that could be detrimental or dangerous, even if they appear to be beneficial.